O problema moral da mentira política em Hannah Arendt - Pereira, Mariana da Silva (2022)
The scope of this work is to discuss the constitution of moral personality in the contemporary context in which facts are despised and contested as a criterion of truth. It started from the observation that the denials of historical facts and events – often treated as matters of opinion – are accompanied by the resurgence of manifestations of hatred, violence and intolerance in the public space. In view of this, it was questioned whether the rejection of factuality would compromise the process by which the person formulates moral judgments, relating to the disposition to “do evil”. To answer this question, Hannah Arendt's considerations on the phenomena (i) of the modern political lie, as a systematic and deliberate denial of facts; and (ii) of the banality of evil, as a result of the absence of thought, or lack of reflection; were claimed as theoretical support. The investigation started from the reconstruction of the arendtian interpretation of the historical and intellectual path of the conflict between truth and politics that culminates in the modern attack on factual truths. Then, we sought to carry out the analysis of the concept of political lie, presenting it, at first, as a strictly political problem, insofar as it aims at the destruction of shared reality - composed, precisely, by a web of facts and events, that links human beings to each other. It was conjectured, however, that the political approach, focusing only on the dimension of human life of coexistence with others, would not be able to exhaust the subject in all its seriousness and extension. Arendt emphasized that in the realm of politics, where secrecy and deliberate falsehood have always played an important role, the quintessential danger is self-deception – in which case the liar becomes a victim of their lies. What the possibility of self-deception highlights is the relationship that the human being establishes with himself, something that, in her view, concerns morality. Nevertheless, Arendt also maintained that moral affronts are powerless to deal with political lies. In this sense, an obstacle to the development of this work was presented, which could only be overcome in the third chapter, dedicated to the discussion of the relationship between morals and politics. It was argued that it would be possible to find, within arendtian theory, elements that point to a kind of political morality, whose central category would be the common world and in which the relationship with oneself and the relationship with others would be interdependent. Since Arendt never actually wrote a book or an essay on political morality, this research had to go through a wide range of texts by the author to identify her, which allowed her to recognize political morality as a type of “moral concern” that permeates the entire set of Arendt's work. Furthermore, the result was the realization that contempt for the facts is what makes fruitful the appearance of what Arendt called extreme and unlimited evil, which takes the form of banality. Appreciated in the light of arendtian political morality, the political lie was revealed, therefore, as a problem, in addition to being political, moral, whose confrontation requires the reconciliation of thought with reality.